Fossil ‘Sphinctozoa’: Chambered Sponges (Polyphyletic) - Senowbari-Daryan, Baba; García-Bellido, Diego C. (Systema Porifera, 2002)
‘Sphinctozoa’ Steinmann (Porifera, chambered sponges), including ‘Thalamida’ de Laubenfels, is a polyphyletic and nearly completely extinct group of taxonomically different sponges that evolved independently several times during the history of the Earth, with only a single Recent extant genus (Vaceletia). They are characterized by an external rigid skeleton and a chambered organization. The morphological and structural characteristics of these various chambered sponges are discussed here. A classification, based on all characteristics, is proposed and the problems of classification are addressed. All genera and species of chambered sponges described as ‘Sphinctozoa’up to the year 2000 are listed with their stratigraphic range and geographic distributions. This fauna includes over 140 genera in nine orders and 42 families.
UnivIS-Import:2017-11-07:Pub.2002.nat.dgeo.IGM.LP.biblio
Keywords: Porifera; ‘Sphinctozoa’; Demospongiae; Calcarea; Hexactinellida; Archaeocyatha